2018
DOI: 10.1039/c8lc00717a
|View full text |Cite
|
Sign up to set email alerts
|

High-yield paper-based quantitative blood separation system

Abstract: Interest in developing paper-based devices for point-of-care diagnostics in resource-limited settings has risen remarkably in recent decades. In this paper, we demonstrate what we refer to as “High Yield Passive Erythrocyte Removal” (HYPER) technology, which utilizes capillary forces in a unique cross-flow filtration for the separation of whole blood with performance comparable to centrifuges. As we will demonstrate, state-of-the-art passive blood separation methods implemented in paper-based systems exhibit r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 22 publications
(25 reference statements)
1
55
0
Order By: Relevance
“…Test strips were imaged by a portable imaging device similar to one previously described by Lu et al 21 . Briefly, the device consists of a 5 megapixel 1080p HD CMOS camera (Raspberry Pi, Cambridge, UK), focusing lens and LEDs (Thorlabs Inc., Newton, NJ, USA), Raspberry Pi computer board, rechargeable lithium ion battery pack (Adafruit Industries, New York, NY, USA), and cassette tray, all surrounded by a 3D-printed light-tight container.…”
Section: Methodsmentioning
confidence: 99%
“…Test strips were imaged by a portable imaging device similar to one previously described by Lu et al 21 . Briefly, the device consists of a 5 megapixel 1080p HD CMOS camera (Raspberry Pi, Cambridge, UK), focusing lens and LEDs (Thorlabs Inc., Newton, NJ, USA), Raspberry Pi computer board, rechargeable lithium ion battery pack (Adafruit Industries, New York, NY, USA), and cassette tray, all surrounded by a 3D-printed light-tight container.…”
Section: Methodsmentioning
confidence: 99%
“…developed a paper-based system which can detect ferritin from full blood using a series of papers with different pore sizes. The authors found the methodology comparable in quality to standard centrifugation for blood separation [123].…”
Section: Challenges Of Paper-based Assaysmentioning
confidence: 99%
“…At present, several ICT kits are available for assaying analytes in WBS. Most of these kits use a plasma-separation membrane for trapping hematocytes and only plasma migrates into a test strip membrane [ 23 , 39 , 40 , 41 ]. However, in our preliminary experiments, the plasma-separation membrane (Cytosep 1660) did not work for trapping hematocytes as expected.…”
Section: Discussionmentioning
confidence: 99%